Fatal Outcome of Suicidal Multi-Substance Ingestion Involving Sodium Nitrate and Nitrite Toxicity: A Case Report and Literature Review - Kaubrytė, Sofija Saulė; Chmieliauskas, Sigitas; Salyklytė, Giedrė; Laima, Sigitas; Vasiljevaitė, Diana; Stasiūnienė, Jurgita; Petreikis, Paulius; Badaras, Robertas (Acta medica Lituanica, 2025)
Background: Nitrate and nitrite toxicity, particularly from sodium nitrite and sodium nitrate ingestion, has become a critical public health issue due to its role in accidental poisoning, foodborne exposure, and intentional self-harm. Sodium nitrite, commonly used in food preservation, is increasingly linked to suicide, with online resources providing accessible information on lethal dosages. This trend underscores an urgent need for regulatory action and preventive strategies. This report details a fatal case of nitrate and nitrite toxicity in a 19-year-old female, presenting a complex toxicological profile involving ethyl alcohol, amphetamines, and additional pharmaceuticals.Materials and methods: A systematic literature search was conducted across PubMed and Google Scholar databases, spanning articles published over a period of the last 10 years, utilizing keywords relevant to the topic under consideration and their combinations. 58 pertinent articles were selected, supplemented by data from the Lithuanian State Forensic Medicine Service, involving a clinical case. Autopsy findings, toxicological analyses, and contextual details were meticulously examined to elucidate the mechanism and circumstances of death.Case presentation: A 19-year-old female was found deceased in her home, alongside a suicide note indicating intent to self-harm through ingestion of sodium nitrate, sodium nitrite, and multiple medications. The autopsy findings included cherry-brown lividity, dark, non-coagulated blood within the heart chambers, and significant multi-organ congestion, consistent with methemoglobinemia and systemic hypoxia. Toxicology results confirmed a blood alcohol concentration of 1.22‰, with trace levels of amphetamine, atropine, and quetiapine, while nitrites detected in the gastric contents confirmed sodium nitrite as a primary toxic agent. The toxic synergy of these substances ultimately led to fatal multi-organ compromise.Conclusions: This case emphasizes the serious risks associated with nitrate and nitrite ingestion, particularly in instances of intentional overdose facilitated by readily accessible online information on lethal dosages. The autopsy findings reveal characteristic signs of methemoglobinemia and systemic hypoxia; however, a thorough forensic assessment must also consider additional factors, including the presence of a suicide note, the scene context, and any substances collected at the location.Lessons: Due to the inherent instability of nitrite in blood, its post-mortem detection is often challenging, thereby complicating toxicological confirmation. The increasing accessibility and misuse of sodium nitrite underscore an urgent need for regulatory oversight, public awareness, and enhanced preventive measures to address the rising incidence of intentional sodium nitrite toxicity, particularly within at-risk populations.
Keywords: nitrate; nitrite; poisoning; suicide